2021
DOI: 10.3390/su131911019
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Ethanol Bio-Refinery Product as a Soy Bean Alternative in Diets for Fast-Growing Meat Production Species: A Circular Economy Approach

Abstract: The recent conceptual pivot from bioethanol production to ethanol biorefining has led to development of protein derived by fractionating the non-ethanol streams post fermentation within the plant. The aim of this study was to identify the effect of replacing dietary soy with corn-fermented protein (CFP) on performance of fast-growing meat species and the impact on the carbon footprint associated with the feed for each species. The study contains trials on 3 species, broiler, turkey and salmon. In trial one, 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…It is forecasted that global food production needs to increase by at least 70% by 2050 to feed the growing global population; therefore, Available at www.veterinaryworld.org/Vol.16/October-2023/3.pdf industrial-scale agricultural activities such as poultry production could be a potential priority [5]. The rapid growth and efficient absorption of feed by poultry ensures the production of poultry meat with a relatively low carbon footprint [6][7][8]. A significant decrease in the demand for rice, an increasing share of palm oil in the global fat and oil markets, and a continued shift to poultry as the dominant form of meat consumption are predicted by 2050 [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is forecasted that global food production needs to increase by at least 70% by 2050 to feed the growing global population; therefore, Available at www.veterinaryworld.org/Vol.16/October-2023/3.pdf industrial-scale agricultural activities such as poultry production could be a potential priority [5]. The rapid growth and efficient absorption of feed by poultry ensures the production of poultry meat with a relatively low carbon footprint [6][7][8]. A significant decrease in the demand for rice, an increasing share of palm oil in the global fat and oil markets, and a continued shift to poultry as the dominant form of meat consumption are predicted by 2050 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, there has been a growing interest in the use of humus and its biologically active principles in livestock farming. Several scientific studies on feed absorption efficiency in poultry farming [2,6,8,10,[17][18][19][20][21][22] have shown a positive effect on the quality of meat and eggs and livestock health. Some research studies have found that various feed additives and biologically active principles included in the poultry diet increased the productivity of poultry, increased feed absorption efficiency, and consequently reduced production cost per kilogram of meat produced [10,23].…”
Section: Introductionmentioning
confidence: 99%